2020
DOI: 10.1080/12298093.2020.1812150
|View full text |Cite
|
Sign up to set email alerts
|

Novel Antihypertension Mechanism of β-Glucan by Corin and ANP-Mediated Natriuresis in Mice

Abstract: Many of the b-glucans are known to have antihypertensive activities, but, except for angiotensin-converting enzyme II inhibition, the underlying mechanisms remain unclear. Corin is an atrial natriuretic peptide (ANP)-converting enzyme. Activated corin cleaves pro-ANP to ANP, which regulates water-sodium balance and lowers blood pressure. Here, we reported a novel antihypertensive mechanism of b-glucans, involved with corin and ANP in mice. We showed that multiple oral administrations of b-glucan induced the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Therefore, these peptides serve as good markers to assess patients with suspected acute heart failure and help with the diagnosis. ANP stimulates the kidney to increase its excretion and cause blood vessels relaxation [ 33 , 34 ]. When the blood volume increases, BNP or Ventricular Natriuretic Peptide is secreted in heart ventricles by cardiomyocytes, causing stretching to the ventricles [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these peptides serve as good markers to assess patients with suspected acute heart failure and help with the diagnosis. ANP stimulates the kidney to increase its excretion and cause blood vessels relaxation [ 33 , 34 ]. When the blood volume increases, BNP or Ventricular Natriuretic Peptide is secreted in heart ventricles by cardiomyocytes, causing stretching to the ventricles [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the biological activities mentioned above, β-D-glucan from Ganoderma species exerts other bioactivities, including antimicrobial [42], hepatoprotective [65], anticoagulant [106], antihypertension [107] properties. Meanwhile, Pillai et al showed [108] that β-D-glucan from G. lucidum exhibited a radioprotective activity with a DNA repairing capacity in human lymphocytes exposed to γ-radiation.…”
Section: Othersmentioning
confidence: 99%